Velar Tap in Dàgáárè - Akinbo, Samuel; Angsongna, Alexander; Ozburn, Avery; Schellenberg, Murray; Pulleyblank, Douglas (My University, 2022)
Bodomo (1997) describes intervocalic velar [ɡ] in Dàgáárè as fricative [ɣ]. With 42 tokens of intervocalic [ɡ] from a native speaker of Dàgáárè, we investigated the acoustic and articulatory features of the Dàgáárè intervocalic velar [ɡ] using ultrasound images, waveforms, spectrograms, and palatogram. The results of the study suggest that Dàgáárè intervocalic [ɡ] is not a fricative but a velar with strong tap-like features, a previously unattested sound in natural language (Ladefoged 1990). Following from this, we conclude that Dàgáárè intervocalic velar [ɡ] is not a fricative but a tap.
Keywords: Dàgáárè; Velar Tap; intervocalic velar; natural language